The SAR analysis of dietary polyphenols and their antagonistic effects on bortezomib at physiological concentrations - Van, Tran Tran Thi; Chang, Hsun-Shuo; Wu, Ho-Cheng; Lu, Chung-Kuang; Huang, Hui-Chi; Korinek, Michal; Hsiao, Hui-Hua; Yen, Chia-Hung (Frontiers in Pharmacology, 2024)
Bortezomib (BTZ), a primary treatment for MM, but its effectiveness can be reduced by interactions with vicinal diol moieties (VDMs) in polyphenols. Despite this, it’s debated whether BTZ therapy necessitates avoiding polyphenol-rich products, given the low bioavailability of polyphenols. Additionally, it remains unclear whether the structure of polyphenols contributes to their BTZ antagonism. Therefore, our study aims to unravel the structure-activity relationship of dietary polyphenols and their BTZ antagonism at daily diet-achievable physiological concentrations. By cell viability assays, we found a positive correlation between the number of VDMs in gallotannins and their BTZ antagonism. Moreover, the origin and configuration of VDMs, rather than the total VDM concentration, play a pivotal role in the combined antagonistic effects against BTZ in gallotannins. Additionally, ChemGPS-NP analysis indicated that the aromaticity and C-3 hydroxyl group in flavonoids' C-rings enhance their BTZ antagonism. Finally, long-term cytotoxicity assays reveal that gallic acid (GA), epigallocatechin (EGC), and epigallocatechin gallate (EGCG), at their physiological concentrations—attainable through tea consumption—significantly and synergistically antagonize BTZ. Therefore, due to the potential for these polyphenols to reduce the effectiveness of BTZ, it is advisable for MM patients undergoing BTZ treatment to reduce their consumption of foods high in VDM-containing polyphenols.